E.D.R.A., the Argentine facility to simulate radiation damage in space. (January 2019) - Ibarra, M.L.; Garcia, J.A.; Dato, A.; Yaccuzzi, E.; Prario, I.; Filevich, A.; Barrera, M.; Alurralde, M.
Abstract: E.D.R.A. (Ensayos de Daño por Radiación y Ambiente/Test of Radiation and Environmental Damage) is a system composed of a beam line and a vacuum chamber installed at Tandar (a 20 MV Van de Graaff tandem accelerator). It has been designed to analyze devices' behaviour under simulated space conditions. The facility features: large irradiation area with uniform beam current, controlled target temperature in a range from LN2 to 300 °C, good target connectivity by multiple BNC and DB25 feedthrough connectors for in situ measurements and control during sample irradiations, and capability of irradiation under very low fluxes. Using this last feature, it is possible to measure space solar cells under proton irradiation to study Total Non Ionizing Dose (TNID), or semiconductor devices under operation to assess their response to Total Ionizing Dose (TID) or Single Event Phenomena (SEP) effects. Multiple sample studies are easily made by using remotely controlled rotary target holders, and a solar simulator illumination source is also available at the facility. The beam current and its uniformity can be assessed and monitored by a system of multiple, electron suppressed, Faraday cups. For SEP measurements, PIN diodes particle detectors are used. Highlights: An irradiation facility located in Buenos Aires, Argentina is described. Capability to perform tests under simulated space conditions. Studies on main radiation effects on electronic components: TID, TNID and SEP. Multiple samples can be studied by using remotely controlled rotary target holders. III-V solar cells were irradiated with 10 MeV.